Advice for the update of the EU Menu guidance: results of the ERA EU Menu project - Ocké, M (2024)
The availability of detailed and high-quality food consumption data is essential for EFSA's risk assessments. In 2014, EFSA published the EU Menu guidance on collecting such data in a harmonised way. The ERA EU Menu project aims to give evidence-based recommendations for updating the EU menu guidance. Based on a literature review on the landscape of methods and tools available for national dietary surveys, lessons learned through an evaluation of the data collected under the EU menu, and a symposium on ‘Harmonised Food Consumption Data Collection in Europe: Time to Reflect and Plan Ahead’, recommendations for an update of the EU Menu guidance were derived. Regarding the topic organisation and planning, the current guidance seems adequate. It is recommended to stimulate more data collection on subgroups such as pregnant and lactating women, vegetarians, and adults over 74. For dietary assessment, flexibility is recommended to accommodate differences in the appropriateness of using interviewer-administered or self-administered new –technology-based 24-hour dietary recalls or food records. More specific guidance is recommended regarding the aspects of food description using FoodEx2 facets, standardisation of the food propensity questionnaire, quality monitoring and assurance, data transfer and reporting. Such updated guidance is thought to lead to better data quality and better insight in data quality. Moreover, better harmonised data can be achieved with improvements in various EU Menu guidance aspects. For dietary assessment, creating flexibility is needed due to differences in the degree of digitalisation in European societies and to gain more experience in the large-scale application of self-administered dietary assessment methods. It is recommended that EFSA also uses other strategies to obtain good quality and better harmonised data. These could include financial incentives, tender specifications consistent with the EU Menu guidance, and supporting capacity building and the sharing of protocols, materials, and lessons learned between countries.